Analisis faktor-faktor yang mempengaruhi pergantian kantor akuntan publik (auditor switching) - Agus Rianda; Raja Adri Satriawan; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study examined the effects of going concern audit opinion, management change, KAP size, client size and financial distress on auditor switching.The sample of this study is 44 of Manufacturing Companies Listed On The Stock Exchange (BEI) during 2011-2013. Analytical techniques used to perform the hypothesis testing is purposive sampling. Data are analyzed using logistic regression method using SPSS (Statistical Product and Service Solution) 17 version.The results showed that the going concern audit opinion, KAP size, client size and financial distress had a effect to auditor switching. But management change had not effect to auditor switching. Going concern audit opinion showed coefficient -0,291 with the signification values 0,003. This the decision made is to accept hypothesis H1. Management change showed coefficient -0,204 with the signification values 0,287. This the decision made was to reject hypothesis H2. KAP size showed coefficient -0,106 with the signification values 0,000. This the decision made is to accept hypothesis H3. Client size showed coefficient -2,501 with the signification values 0,013. This the decision made was to reject hypothesis H4. And the financial distress showed coefficient 1,453 with the signification values 0,034. This the decision made is to accept hypothesis H5.Keywords : auditor switching, going concern audit opinion, management change, KAP size, client size, financial distress.